Subacute Canine Monocytic Ehrlichiosis in a Two Month Old Siberian-Husky Puppy – Diagnosis and Therapeutic Management - Subramanian, Saravanan; Ganapathy, Selvaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine monocytic ehrlichiosis (CME) caused by E. canis is most pathogenic and transmitted by the tick vector  Riphicephalus sanguineus with non-regenerative anaemia and  thrombocytopenia as common haematological abnormalities  (Piratae et al., 2019). The disease may progress as acute, subacute and chronic, and in acute form, fever, anorexia, ocular  discharge, petechiae, epistaxis, pale mucosae, bleeding  signs, lymphadenopathy, and neurological signs may  be observed (Waner and Harrus, 2013). In chronic phase,  severe pancytopenia due to bone marrow hypoplasia is  characteristic, which leads to severe leukopenia, anaemia,  and thrombocytopenia resulting in death (Angkanaporn et  al., 2022). Usually, the detection of E. canis (morulae) in dogs  by conventional microscopy becomes very difficult owing to  the low parasitaemia (Singh et al., 2021) and thus failure of  detection in an early stage leads to chronic myelosuppressive  form, which is often fatal. Siberian husky is the breed highly  susceptible to CME, however, the incidence in this breed is  rarely reported in India (Singh et al., 2021). This study reports  an early diagnosis of sub-acute ehrlichiosis in a Siberian husky  puppy and it’s successful therapeutic management.
Keywords: anorexia; ocular discharge; petechiae; epistaxis; pale mucosae